Kinetic modeling of carboxylation of propylene oxide to propylene carbonate using ion-exchange resin catalyst in a semi-batch slurry reactor. (31st August 2017) - Jin, Xin; Bobba, Pallavi; Reding, Nicolas; Song, Ziwei; Thapa, Prem S.; Prasad, Guru; Subramaniam, Bala; Chaudhari, Raghunath V.
Highlights: Discovery of unusual CO2 inhibition effect on carboxylation of propylene oxide. Detailed kinetic modeling on propylene oxide conversion to propylene carbonate. Experimental evidence for activation of CO bond on catalyst surface. Comprehensive model derivation and discrimination of various reaction mechanism. Abstract: Kinetic modeling of carboxylation of propylene oxide with CO2 to propylene carbonate has been investigated in a semi-batch slurry reactor. Propylene oxide can be selectively transformed into propylene carbonate (selectivity: 99+%) in the presence of ion exchange resin catalysts with basic functional groups. The effect of reaction temperature (65–95 °C), CO2 pressure (0.5–3.0 MPa), propylene oxide concentration in propylene carbonate (as a solvent) on the carboxylation rates was studied. Experimental results show that CO2 displays inhibition effect on carboxylation reaction at high pressure conditions. For kinetic modeling, three types of rate models were investigated, including two involving Langmuir-Hinshelwood and one modified Eley-Rideal mechanisms. Details of model discrimination and evaluation of kinetic parameters are discussed. Based on the parameter estimation and rigorous model discrimination, it is found that the proposed modified Eley-Rideal rate model describing surface reaction between free PO and adsorbed CO2 on catalyst surface fits the experimental data very well.